Ownership Structure, Tax Risk, and Tax Avoidance in Indonesia Manufacturing Companies 2016-2020 - Mangoting, Yenni; Yuliana, Oviliani Yenty; Valencia, Ellen; Utomo, Claresta Puguh Mettasari (Jurnal Ilmiah Akuntansi dan Bisnis; Vol 17 No 2 (2022), 2022)
There has not been much research on how management uses tax risk to engage in aggressive tax avoidance in an uncertain business environment. This research aims to see how family and institutional ownership influence the relationship between tax risk and tax avoidance as moderating proxies. The study was conducted on manufacturing companies listed on Indonesia Stock Exchange between 2016 and 2020. Thirty-six companies were selected as the sample using the purposive sampling method. This quantitative research used Ordinary Least Square. The results show that family ownership can strengthen the relationship between tax risk and tax avoidance, while institutional ownership fails to moderate. Family shareholders significantly influence company management when selecting how to utilize the tax risk connected with each business strategy. Family shareholders prioritize the protection of the company’s image over maximizing profits with high risk. Keywords: tax avoidance, tax risk, family ownership, institutional ownership, resource based-view theory